Conceptualizing the North: Three Presentations from Norway, Canada, and the United States (2021-04-07) - Maxwell, Kate; Mittner, Lilli; Hammer Stien, Hanne; Horsberg Hansen, Hanna; Moffarr, John; Beard, David; University of Minnesota Duluth. Royal D. Alworth, Jr. Institute for International Studies (2021)
Presentations include: "It matters what worlds world worlds," Kate Maxwell, Lilli Mittner, and Hanne Hammer Stien, UiT The Arctic University of Norway; "There Is No - A (de)colonial project - Or Not?," Hanna Horsberg Hansen, UiT The Arctic University of Norway; "The Canadian North as the Place where Peoples Meet in the Comics of Jeff Lemire," John Moffatt, University of Saskatchewan, David Beard, University of Minnesota Duluth; Free and Open to the public; A CLA and LSBE Passport Event Royal D. Alworth, Jr. Institute for International Studies and UMD Writing Studies Program